KAJIAN EMPIRIS DETERMINAN KONSERVATISME AKUNTANSI DI BURSA EFEK INDONESIA - Putri Angkasawati; Ardiani Ika Sulistyawati; Aprih Santoso (Universitas YPPI Rembang, 2022)
This study aims to empirically examine the factors that influence the application of conservatism in accounting in companies. These factors are leverage, company size, capital intensity, liquidity, growth opportunities, and financial distress found in natural resource and service sector companies listed on the Indonesia Stock Exchange in 2014-2018. This research was conducted with a purposive sampling method. Data collection techniques using secondary data. Data was obtained from natural resource and service sector companies from 2015-2019 which were listed on the IDX. Multiple Linear Regression method using SPSS 25. he results of this study leverage, liquidity and financial distress have a significant effect on accounting conservatism, while company size, capital intensity and growth opportunities do not have a significant effect on accounting conservatism.